![\left\{{{\frac{1}{x}-\frac{1}{y}=\frac{1}{6}}\atop{xy=6}}\right. \left\{{{\frac{1}{x}-\frac{1}{y}=\frac{1}{6}}\atop{xy=6}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B%5Cfrac%7B1%7D%7Bx%7D-%5Cfrac%7B1%7D%7By%7D%3D%5Cfrac%7B1%7D%7B6%7D%7D%5Catop%7Bxy%3D6%7D%7D%5Cright.)
OДЗ: x≠0; y≠0
1)Преобразуем первое уравнение:
![\frac{1}{x}-\frac{1}{y}=\frac{1}{6} \frac{1}{x}-\frac{1}{y}=\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%7D-%5Cfrac%7B1%7D%7By%7D%3D%5Cfrac%7B1%7D%7B6%7D)
![\frac{1}{x}-\frac{1}{y}-\frac{1}{6}=0 \frac{1}{x}-\frac{1}{y}-\frac{1}{6}=0](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%7D-%5Cfrac%7B1%7D%7By%7D-%5Cfrac%7B1%7D%7B6%7D%3D0)
![\frac{6y-6x-xy}{6xy}=0 \frac{6y-6x-xy}{6xy}=0](https://tex.z-dn.net/?f=%5Cfrac%7B6y-6x-xy%7D%7B6xy%7D%3D0)
2) Подставим ху=6
![\frac{6y-6x-6}{6*6}=0 \frac{6y-6x-6}{6*6}=0](https://tex.z-dn.net/?f=%5Cfrac%7B6y-6x-6%7D%7B6%2A6%7D%3D0)
![\frac{y-x-1}{6}=0 \frac{y-x-1}{6}=0](https://tex.z-dn.net/?f=%5Cfrac%7By-x-1%7D%7B6%7D%3D0)
![\frac{y-x-1}{6}*6=0*6 \frac{y-x-1}{6}*6=0*6](https://tex.z-dn.net/?f=%5Cfrac%7By-x-1%7D%7B6%7D%2A6%3D0%2A6)
y=x+1" alt="y-x-1=0=>y=x+1" align="absmiddle" class="latex-formula">
3) Подставим у=x+1 во второе уравнение:
![x*(x+1)=6 x*(x+1)=6](https://tex.z-dn.net/?f=x%2A%28x%2B1%29%3D6)
![x^2+x-6=0 x^2+x-6=0](https://tex.z-dn.net/?f=x%5E2%2Bx-6%3D0)
![D=1-4*1*(-6)=25=5^2 D=1-4*1*(-6)=25=5^2](https://tex.z-dn.net/?f=D%3D1-4%2A1%2A%28-6%29%3D25%3D5%5E2)
![x_1=\frac{-1-5}{2}=-3 x_1=\frac{-1-5}{2}=-3](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7B-1-5%7D%7B2%7D%3D-3)
![x_2=\frac{-1+5}{2}=2 x_2=\frac{-1+5}{2}=2](https://tex.z-dn.net/?f=x_2%3D%5Cfrac%7B-1%2B5%7D%7B2%7D%3D2)
4)
y_1=-3+1=>y_1=-2" alt="x_1=-3;=>y_1=-3+1=>y_1=-2" align="absmiddle" class="latex-formula">
(-3; -2)
y_2=2+1=>y_2=3" alt="x_2=2;=>y_2=2+1=>y_2=3" align="absmiddle" class="latex-formula">
(2; 3)
Ответ: (-3; -2); (2; 3)